Chronological developments in the Old Kingdom tombs in the necropoleis of Giza, Saqqara and Abusir : toward an economic decline during the early dynastic period and the Old Kingdom /: toward an economic decline during the early dynastic period and the Old Kingdom. ([2016]) - Roeten, Leo
No abstract available